Commercializing dairy and forage systems in Ethiopia: An innovation systems perspective - Lemma, T.; Puskur, Ranjitha; Hoekstra, Dirk; Tegegne, Azage (International Livestock Research Institute, 2010)
This paper presents and discusses the results of the analysis of Ethiopian dairy and forage innovation systems. Two factors triggered the need for understanding the innovation systems: Ethiopian dairy subsector has not been able to take-off despite decades of research and development efforts; and the context for the subsector development is changing. The purpose of the research was to identify organizational, institutional and policy options to facilitate market-driven and knowledge-based smallholder dairy development in the country. Specifically, the analysis looked at contextual factors determining opportunities and necessities for innovation; the key innovation systems actors, pattern of interaction between them; coordination mechanisms; and the subsector development policy and strategy. The investigation was based on a survey of actors and their roles and interactions, review of policy, and project documents and available empirical evidence. The research identified constraints and challenges relating to market, supportive services, interaction of actors, inter-organizational coordination, and gaps in the subsector development policy and strategy. Finally,options are identified that can enhance commercialization and innovation. The options include: strengthening dairy cooperatives with emphasis on their business-orientation, linking them, where appropriate, vertically to processors and input suppliers, and strategically linking dairy development intervention to informal markets through food security/food transfer programs and institutionalized school feeding programs; public support for the development of private service and pluralistic service delivery system, alongside strengthening public capacity for performing regulatory and quality assurance functions effectively; formulating national dairy development policy and strategy to ensure coordinated policy implementation on the ground; encouraging the integration of emerging dairy cooperatives at higher levels and capacity building to enable them to demand service, command accountability, and serve as a mouthpiece of producers; capitalizing on the on-going Business Process Re-engineering for revising the prevailing reward systems in public research and extension to encourage innovation and impactorientation; creating incentive system such as leverage fund and competitive grant to encourage intervention-based public–private innovation partnership; and strengthening dairy platform at woreda and/or milkshed level for achieving of better impact through continuous incremental improvements and to facilitate scaling out and up of successful experience to achieve wider impact and inform higher policymaking.